Thermal stability of stealth and de Sitter spacetimes in scalar-tensor gravity - Giardino, Serena; Giusti, Andrea; Faraoni, Valerio (The European physical journal. C, Particles and fields, 2023)
Stealth solutions of scalar-tensor gravity and less-known de Sitter spaces that generalize them are analyzed regarding their possible role as thermal equilibria at non-zero temperature in the new first-order thermodynamics of scalar-tensor gravity. No stable equilibria are found, further validating the special role of general relativity as an equilibrium state in the landscape of gravity theories, seen through the lens of first-order thermodynamics.
Gesehen am 10.11.2023